A research on fatigue life of front axle beam for heavy-duty truck. (January 2016) - Zhang, Min; Ji, Xiangfei; Li, Lijun
Abstract: Front axle is one of the important parts of vehicle. The Fatigue Tool in ANSYS Workbench software is used to analyze its strength situations and fatigue life. The dangerous area of beam is determined, which provides a certain basis for structure improvement. In addition, in view of three kinds of working condition often used, a combined fatigue simulation of multiworking conditions is carried out. The influence of different conditions on fatigue life is studied. Finally, fatigue life of front axle containing crack is investigated to analyze the effect of crack parameters such as length and depth on fatigue life.